Profile-oriented algorithms teaching: a proposed methodology - Moreira, Fernando (2015)
One of the first challenges faced by students who are starting a Computer Science degree is to acquire skills which allow them solving real life problems through the use of algorithms. Such skills require the development of the ability to abstract as well as to apply algorithms development techniques. As a result of the difficulty in obtaining these competences, there are high failure and dropout rates in courses of related to this field of study. In order to solve this problem, we propose a methodology based on VARK questionnaire to define the students' profile and, consequently, what are their appropriate educational materials and tools